The 1st International Electronic Conference on Biosensors 2020
DOI: 10.3390/iecb2020-07067
|View full text |Cite
|
Sign up to set email alerts
|

Electrochemical DNA Detection Methods to Measure Circulating Tumour DNA for Enhanced Diagnosis and Monitoring of Cancer

Abstract: Liquid biopsies are becoming increasingly important as a potential replacement for existing biopsy procedures which can be invasive, painful and compromised by tumour heterogeneity. This paper reports a simple electrochemical approach tailored towards point-of-care cancer detection and treatment monitoring from biofluids using a label-free detection strategy. The mutations under test were the KRAS G12D and G13D mutations, which are both important in the development and progression of many human cancers and whi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 36 publications
1
3
0
Order By: Relevance
“…It has been observed that these effects can be reversed when micro-or nanoscale electrodes are employed [20,46], but for this study, the electrodes used were comfortably on the macro scale (diameter = 2.95 mm). For nanomolar (>10 nM) and micromolar concentrations, an increase in the peak current following hybridisation was consistently observed (and has also been observed in other data from our lab involving SPCEs) [1] for carbon electrodes which is likely explained by the high surface density of hybridised DNA amplicons changing the interfacial properties of the electrode and, therefore, altering the electrochemical response. The underlying physical mechanism of this effect is actively under investigation.…”
Section: Dna Sensor Hybridisation Specificitysupporting
confidence: 87%
See 3 more Smart Citations
“…It has been observed that these effects can be reversed when micro-or nanoscale electrodes are employed [20,46], but for this study, the electrodes used were comfortably on the macro scale (diameter = 2.95 mm). For nanomolar (>10 nM) and micromolar concentrations, an increase in the peak current following hybridisation was consistently observed (and has also been observed in other data from our lab involving SPCEs) [1] for carbon electrodes which is likely explained by the high surface density of hybridised DNA amplicons changing the interfacial properties of the electrode and, therefore, altering the electrochemical response. The underlying physical mechanism of this effect is actively under investigation.…”
Section: Dna Sensor Hybridisation Specificitysupporting
confidence: 87%
“…In recent years, analytical electrochemistry has emerged as a powerful tool for the rapid in-vitro analysis of biological analytes for the early detection of certain diseases, such as cancer [ 1 ]. Cancer is a genetic disease by nature, caused by mutations in certain genes thereby resulting in cellular malfunction [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations